Physical And Organolepic Test Of Free-Range Chicken Meat Baksok With Sago Starch Addition At Different Concentrations - Amalyadi, Rezki (Jurnal Peternakan Nusantara, 2025)
Sago flour contains high starch and low price so it can be used as a substitute in making meatballs. The large amount of carbohydrate content (starch) contained in sago flour as a filler makes starch ingredients high and cheap so that it can be used as a substitute in making meatballs. This study aims to determine the effect of the addition of sago flour with different concentrations on the Physical and organoleptic tests of free-range chicken meatballs. This research was carried out in the laboratory room of the Faculty of Life Sciences and Technology, Sumbawa University of Technology, West Nusa Tenggara. This research was carried out in June 2024. Data analysis used a Complete Random Design (CRD) with 4 treatments and 5 adventures. The treatment given in making kampung chicken meatballs is the addition of different chewy ingredients. The results of the study showed that the Physical and organoleptic properties of free-range chicken meatballs with the addition of free-range chicken at different concentrations had an effect on the pH of P0 15% 6.14 ± 0.8a, Taste P0 3.40 ± 0.86a, Color P3 3.16 ± 1.37a. while in the variables of cooking succulents, the yield, aroma and texture did not differ significantly (P>5%).